Pendekatan Etnopedagogi Sebagai Media Pelestarian Kearifan Lokal - Muzakkir Muzakkir (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2021)
English:Pidie is one of the districts that has a diversity and rich culture. According to the official website of the Pidie district government, generally Pidie cultural objects have ancient manuscripts, oral traditions, customs, rituals, traditional knowledge, traditional technology, arts, folk games, traditional sports and cultural heritage. All these cultures become learning capital that students bring to school. Ethnopedology is an approach in culture-based education. The use of ethnopedology’s in learning more strategically can be done by means of education based on cultural values ??for teaching and learning in context. The use of culture in learning is in the form of Seudati Dance in Mathematics learning, manuscripts and cultural heritage in language learning, Kupiah riman in Arts/crafts, customs as a medium for social science learning, Megeude – geude in EEPIS learning. Bahasa: Pidie Merupakan salah satu daerah yang memiliki keberagaman dan kekayaan budaya. Menurut Situs resmi Pemerintah kabupaten Pidie secara umum objek budaya Pidie memiliki Manuskrip Kuno, Tradisi Lisan, Adat Istiadat, Ritus, Pengetahuan Tradisional, Teknologi Tradisional, Seni, permainan rakyat, Olahraga Tradisional dan cagar budaya. Semua budaya ini menjadi modal belajar yang dibawa siswa ke sekolah. Etnopedagogi adalah sebuah pendekatan dalam pendidikan yang berbasis budaya. Pemanfaatkan etnopedagogik dalam pembelajaran secara lebih strategis dapat dilakukan dengan cara pendidikan berbasis nilai budaya bagi pengajaran dan pembelajaran dalam konteks. Pemamfaatan budaya dalam pembelajaran berupa Tari seudati dalam pembelajaran Matematika, manuskrip dan cagar budaya dalam pembelajaran Bahasa, kupiah riman dalam Seni/prakarya, adat istiadat sebagai media pembelajaran ilmu sosial, Megeude – geude dalam pembelajaran PENJASKES.